Ang tipo kong lalaki an audience study of female fans' perception and reception of masculinity of local male matinee idols - Argante, Christine Mae Regala 1993 (2014)
"In a patriarchal society where various agents contribute and reproduce meanings masculinity in both context and understanding had evolved through time. In a published book entitled Manhood in the Making. David Gilmore defined masculinity as the approved way of being a male in a given society. This process of approval comes hand in hand with different agents and attributes that reinforce the gender standards and norms that help in cultivating the reception of the audience in consuming texts. The media have always served as an important agent in manifesting and reinforcing society's accepted gender roles; male local celebrities often play and embody these roles that are perceived and accepted by the audience. But with the rise of different form of media and communication, the definition of the 'lalaki' has gone through drastic changes that brought deviations and transformations in today's Philippine culture and society. This study tried to define the current trends of masculinity in the Philippines using female fans' reception of local matinee idols. The audience perception and reception of fans were measured and analyzed using Stuart's Hall reception theory and the concept of hegemonig masculinity."